Evaluation of Asset and Liability Management Strategies in Companies from an Islamic Perspective - Maryam Bte Badrul Munir; Norfhadzilahwati Binti Rahim (Universitas Muhammadiyah Surabaya, 2022)
Purpose of the study effective asset and liability management analysis is essential to risk management, especially now that banks are performing better. After the 2008–2009 global financial crisis, banks began to assess the risk associated with their assets and liabilities. The banks then established ALCO, an acronym for Asset and Liability Committee. ALCO is permitted to conduct asset and liability management analyses. This theory is essential for the continuation of performance research, particularly for raising awareness of the significance of ALCO and ALM. Asset and liability management is believed to be one technique for businesses to monitor the emergence of performance-harming hazards. Before and after 2008, the bank's annual report illustrated the evolution of ALM and ALCO. This research will examine papers discussing the importance of asset and liability management for increasing a bank's performance. The method employs descriptive analysis based on document analysis technology. It employs Asset and Liability Management keywords from the Mendeley and Google Scholar databases. This study evaluates bank assets and liabilities from 2008 to 2016 using Mendeley software. 47.753.293 items were searched. This research only covered 250 banking performance papers. 25 of 250 articles from 2008 to 2016 discussed banks. Each paper contains a title, year of publication, methodological type (quantitative or qualitative), and objective